Sustainable alternative feed ingredients: effects of palm kernel cake and decanter cake on broiler growth and production performance - Azizi, Mohammad Naeem; Loh, Teck Chwen; Chung, Eric Lim Teik; Ab Aziz, Muhamad Faris; Foo, Hooi Ling; Liu, Jiaxiang; Izuddin, Wan Ibrahim (Springer Science and Business Media B.V., 2026)
This study evaluated the potential of palm kernel cake (PKC) and decanter cake (DC) as sustainable feed ingredients for broiler chickens. A total of 1,200 one-day-old male chicks were reared for a 35-day experimental period. The birds were randomly allocated into 15 dietary treatment groups, with each group consisting of 8 replicates and 10 birds per replicate. Treatment 1 is considered the control diet, without inclusion of PKC or DC. Treatments 2 to 8 contained 2% to 14% PKC in 2% increments, while treatments 9 to 15 included DC at the same inclusion levels. Statistical analyses were conducted using the General Linear Model (GLM) in Statistical Analysis System (SAS) software. One-way analysis of variance (ANOVA) was used to determine the treatment effects, and Duncan’s multiple range test was used to determine significant differences between treatment means at p < 0.05. The results showed that higher inclusion levels of both by-products, particularly above 6%, adversely affected broiler growth performance by reducing (p < 0.05) birds’ body weight (BW), carcass weight, average daily gain (ADG) and European Broiler Index (EBI), while increasing (p < 0.05) feed intake (FI) and feed conversion ratio (FCR). Likewise, growth hormone receptor (GHR) and insulin-like growth factor-1 (IGF-1) transcription were unchanged, indicating that performance effects stemmed from nutritional rather than endocrine factors. However, meat quality traits such as pH and water-holding capacity remained unaffected (p > 0.05). This study suggests that DC and PKC can be included in broiler diets at levels up to 4–6%, as higher levels may negatively impact growth performance and carcass characteristics.